Acute Effects of High-Intensity Aerobic Exercise on Motor Cortical Excitability and Inhibition in Sedentary Adults - Hendy, Ashlee M.; Andrushko, Justin W.; Della Gatta, Paul A.; Teo, Wei-Peng (Frontiers in Psychology, 2022)
Transcranial magnetic stimulation studies have demonstrated increased cortical facilitation and reduced inhibition following aerobic exercise, even when examining motor regions separate to the exercised muscle group. These changes in brain physiology following exercise may create favorable conditions for adaptive plasticity and motor learning. One candidate mechanism behind these benefits is the increase in brain derived neurotropic factor (BDNF) observed following exercise, which can be quantified from a venous blood draw. The aim of this study was to investigate changes in motor cortex excitability and inhibition of the upper limb, and circulating BDNF, following high intensity interval training on a stationary bicycle. Nineteen sedentary adults participated in a randomized crossover design study involving a single bout of high intensity interval cycling for 20 mins, or seated rest. Venous blood samples were collected, and transcranial magnetic stimulation was used to stimulate the extensor carpi radialis, where motor evoked potentials were recorded pre and post each condition. Following exercise, there was a significant increase (29.1%, p < 0.001) in corticospinal excitability measured at 120% of resting motor threshold, and a reduction in short-interval cortical inhibition (SICI, quantified as 86.2% increase in the SICI ratio, p = 0.002). There was a non-significant (p = 0.125) 23.6% increase in BDNF levels. Collectively, these results reflect a net reduction in GABAergic synaptic transmission and increased glutamatergic facilitation, resulting in increased corticospinal excitability. This study supports the notion that acute high intensity exercise provides a potent stimulus for inducing cortical neuroplasticity, which may support enhanced motor learning.